Manajemen Zakat di Masa Awal Islam - Reni Reni; Rahmawati Muin (Universitas Muhammadiyah Makassar, 2023)
One of the most appropriate criteria used to describe how zakat is managed ideally is by tracing how zakat was managed in the early Islamic era. This is the background for conducting this research, especially to find out the zakat management policies in the early period of Islam and are currently projected as state standards. This research is a library research with a descriptive analysis approach. Based on the data obtained, it can be understood that, during the time of Rasulullah SAW, the management of zakat was carried out individually with the help of friends who were assigned to collect zakat. Even during the era of Abu Bakar Al-Siddiq, the policy of paying zakat was clarified and tightened. As a result, Muslims who hesitate to assume this responsibility will be seen as enemies of Islam. Although the implementation of this policy was facilitated during the reign of Uthman bin Affan, it does not mean that the (Islamic) state does not have the authority to manage zakat. Keywords: Zakat, The Period of the Prophet, Islamic Economics